2019
DOI: 10.18502/kls.v4i10.3703
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden and Non-Adherence Tuberculosis Treatment in Indonesia: Systematic Review

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…In developing countries, patients with low socioeconomic status often face the challenge of balancing competing priorities. These competing priorities might require allocating limited resources to meet the needs of other family members, such as the children or parents catered for ( Killewo, 2002 ; World Health Organization, 2003 ; Diniawati and Wibowo, 2018 ; Mahara et al, 2018 ). Healthcare team-related factors (40 items) explored the effects of the patient-provider relationship, and more investigations are needed concerning the impact of the healthcare team and system-related factors on non-adherence.…”
Section: Resultsmentioning
confidence: 99%
“…In developing countries, patients with low socioeconomic status often face the challenge of balancing competing priorities. These competing priorities might require allocating limited resources to meet the needs of other family members, such as the children or parents catered for ( Killewo, 2002 ; World Health Organization, 2003 ; Diniawati and Wibowo, 2018 ; Mahara et al, 2018 ). Healthcare team-related factors (40 items) explored the effects of the patient-provider relationship, and more investigations are needed concerning the impact of the healthcare team and system-related factors on non-adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies did not clearly indicate an association between adherence and economic outcomes (Diniawati and Wibowo, 2018;Chimeh et al, 2020). One study suggested that good adherence results in lower medical costs, with the medical cost for patients showing an outcome of treatment completion was estimated to be 17% higher than the cost estimate of the Frontiers in Pharmacology frontiersin.org national guideline-based treatment in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals and/or families are sometimes compelled to sell valuable personal or family assets, or to borrow money to meet the costs associated with TB infections, with catastrophic consequences for their ongoing lives (11,17).In the worst cases, individuals or families (in the lowest income quintile) nd themselves compelled to further reduce their spending on essentials such as food, school fees, and transportation (11,16,(18)(19)(20). TB care-seeking costs have been shown, in several countries, to have signi cant negative impacts on individuals (patients, survivors) and their families' wellbeing, and to present challenges for continued compliance with recommended care and treatment schedules (21). A recent national survey in Tanzania demonstrated that, of 777 TB-affected households, about 45 percent reported having faced catastrophic costs (18).…”
Section: Introductionmentioning
confidence: 99%